2014
DOI: 10.1097/moo.0000000000000047
|View full text |Cite
|
Sign up to set email alerts
|

Managing dysphonia in occupational voice users

Abstract: This review reinforced the need for large population studies of professional voice users; new data highlighted important factors specific to each group of voice users. Interventions directed at student teachers are necessities to not only improving the quality of future professionals, but also to avoid the frustration and limitations associated with chronic voice problems. The causative relationship between the work environment and voice disorders has not yet been established. Randomized controlled trials are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 57 publications
0
21
0
11
Order By: Relevance
“…Entretanto, a alteração no comportamental vocal, devido ao mau uso e/ou uso abusivo da voz somada a fatores ambientais precisam ser mais bem investigadas em futuros estudos, uma vez que os problemas de voz são multifatoriais 18,25 . A tabela 3 mostra que houve associação da qualidade vocal alterada com grau de alteração leve.…”
Section: Discussionunclassified
“…Entretanto, a alteração no comportamental vocal, devido ao mau uso e/ou uso abusivo da voz somada a fatores ambientais precisam ser mais bem investigadas em futuros estudos, uma vez que os problemas de voz são multifatoriais 18,25 . A tabela 3 mostra que houve associação da qualidade vocal alterada com grau de alteração leve.…”
Section: Discussionunclassified
“…Despite being frequently used, most protocols, and their respective translations, cultural adaptations (3) , and validation to Brazilian Portuguese (4)(5)(6)(7)(8)(9) , are still addressed to specific conditions. Therefore, they are not adequate for individuals with healthy voices, such as voice professionals, who deserve specific evaluation (10)(11)(12) . To fill this gap, the protocol Evaluation of the Ability to Sing Easily (EASE) was created (13) to assess the perception of the singers about the status of their singing voice after a performance, thus promoting the immediate overview about the use of voice.…”
Section: Introductionmentioning
confidence: 99%
“…In other study, which involved 675 teachers of both sexes, it was observed that 16.4% of them were undergoing vocal treatment, 71% had sought medical otolaryngologist (ENT), 36.2% went on leave for voice problems and more than half of the sample (52.2%) had never received specific training for the voice (3) . Faced with such evidence on the vocal conditions of teachers and the high dysphonia index, the literature reinforces the need to conduct randomized clinical trials with this population to test different types of interventions by checking which ones are most effective (6,7) . Scientific evidence about the different types of intervention will work so that they can be used more appropriately and safely by speech and language therapists, with the certainty of generating benefits for patients and, thus, indirectly, to society in general (6,7) .…”
Section: Introductionmentioning
confidence: 99%
“…Faced with such evidence on the vocal conditions of teachers and the high dysphonia index, the literature reinforces the need to conduct randomized clinical trials with this population to test different types of interventions by checking which ones are most effective (6,7) . Scientific evidence about the different types of intervention will work so that they can be used more appropriately and safely by speech and language therapists, with the certainty of generating benefits for patients and, thus, indirectly, to society in general (6,7) . Knowledge about effective techniques provided by randomized clinical trials will contribute to the prevention/treatment of work-related voice disorder (WRVD) as well as to the health promotion of teachers (1,6) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation